Environmental Issues and Sustainable Development - Sarvajayakesavalu, Suriyanarayanan; Charoensudjai, Pisit (IntechOpen, 2021)
In recent years, attention to climate change and its associated impacts on economic and social development has increased significantly. Extreme weather conditions worldwide are threatening the survival of sensitive species and habitats. The situation is so dire that governments, academia, and non-governmental organizations across the globe are actively working to meet the United Nations Sustainable Development Goals. This book enhances understanding of environmental changes and the relative response to the socio-economic challenges of development. It provides a comprehensive overview of the impact of environmental change on natural resources and the climate, as well as discusses waste management and sustainable solutions.